Atomically dispersed Co₂ -N₆ and Fe-N₄ costructures boost oxygen reduction reaction in both alkaline and acidic media - Wang, Zhe (2022)
Polynary transition-metal atom catalysts are promising to supersede platinum (Pt)-based catalysts for oxygen reduction reaction (ORR). Regulating the local configuration of atomic catalysts is the key to catalyst performance enhancement. Different from the previously reported single-atom or dual-atom configurations, a new type of ternary-atom catalyst, which consists of atomically dispersed, nitrogen-coordinated Co-Co dimers, and Fe single sites (i.e., Co2 -N6 and Fe-N4 structures) that are coanchored on highly graphitized carbon supports is developed. This unique atomic ORR catalyst outperforms the catalysts with only Co2 -N6 or Fe-N4 sites in both alkaline and acid conditions. Density functional theory calculations clearly unravels the synergistic effect of the Co2 -N6 and Fe-N4 sites, which can induce higher filling degree of Fe-d orbitals and favors the binding capability to *OH intermediates (the rate determining step). This ternary-atom catalyst may be a promising alternative to Pt to drive the cathodic ORR in zinc-air batteries.